Growth Components -atJuvenile Stage and their RelationshipÂ· with Height at Different Growth Stages in Acacia albida - Pancholy, Anjly; Jindal, S K; Singh, Manjit; Rajora, M P (Annals of Arid Zone, 2016)
Seven accessions of Acacia albida sown in nursery in May 1994 were evaluated at 7-month and 8-month old seedling stage in nursery for root and shoot traits. Simultaneously two-month-old seedlings were planted in the field to assess the juvenile-adult correlation by observing it for another twelve years. There were significant differences for collar diameter, root fresh weight, root dry weight, shoot fresh weight, shoot dry weight and total dry biomass per plant at both. the stages of the seedlings. During nursery stage, the heritability was low. for most of the characters. Expression of relationships was more with age of the plants. The path analysis showed that dry root weight was an important character for dry shoot weight. Shoot length and root-shoot length ratio of the seedlings in the nursery contributed maximum to the height of the plants in the field. Key words: Growth components, juvenile stage, height, Acacia. albida.